Comparison of energy systems in Small Island Developing States. (October 2018) - Surroop, Dinesh; Raghoo, Pravesh; Bundhoo, Zumar M.A.
Abstract: Small Island Developing States (SIDS) have been amongst the most neglected group with regard to energy access until recently when several voices were raised to highlight the vulnerabilities of these small nations. Since then, their levels of energy access have become the focus of significant attention. These levels vary over a wide range, where some SIDS still have a low energy access although they may have the resources. The energy mix for electricity production is mostly dominated by fossil fuels where the transportation cost results in high cost of fossil fuels and this leads to a high cost of electricity. Highlights: SIDS are very diverse in terms of size, population and economic development. SIDS are similar in environmental challenges and they are all vulnerable to the changing environment. SIDS have a low energy access although they may have resources. The energy mix for electricity production is mostly dominated by fossil fuels. The cost of electricity is highest the SIDS.